2020
DOI: 10.20961/agsjpa.v22i2.44151
|View full text |Cite
|
Sign up to set email alerts
|

Induksi Mutasi Kara Benguk (Mucuna pruriens L.) Menggunakan Iradiasi Sinar Gamma

Abstract: <p>Breeding kara benguk with mutation induction techniques using gamma ray radiation is expected to produce genetic diversity. The purpose of the study is to determine the value of Lethal Dose 50 (LD50) and obtain the genetic diversity of the kara benguk plant. The research was conducted at PAIR BATAN and Agrotechnology experiment, Universitas Labuhanbatu from May-July 2020. The planting material used was kara benguk seeds. The method used was Randomized Complete Group Design (RCGD) with one factor which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The comparation of seedling between M1 mutans and Cipedak as a control was indicated that treated seedlings were decrease in the variable of petiole length, leaf blade length, and leaf blade width. The changes in the size of plant organ to become shorter due to mutations caused by gamma ray irradiation also occurred in the study of mutations in winged-bean (Saragih et al, 2020), sunflower (Monikasari et al, 2018), leunca (Saragih & Aisyah, 2019), avocado (El-mageid & Al-Kfrawey, 2018), and mangosteen (Widiastuti et al, 2010). The dendogram of 14 avocado accessions that were tested based on macro-morphological characters showed phenotypic differences up to a coefficient of 33%.…”
Section: Resultsmentioning
confidence: 85%
“…The comparation of seedling between M1 mutans and Cipedak as a control was indicated that treated seedlings were decrease in the variable of petiole length, leaf blade length, and leaf blade width. The changes in the size of plant organ to become shorter due to mutations caused by gamma ray irradiation also occurred in the study of mutations in winged-bean (Saragih et al, 2020), sunflower (Monikasari et al, 2018), leunca (Saragih & Aisyah, 2019), avocado (El-mageid & Al-Kfrawey, 2018), and mangosteen (Widiastuti et al, 2010). The dendogram of 14 avocado accessions that were tested based on macro-morphological characters showed phenotypic differences up to a coefficient of 33%.…”
Section: Resultsmentioning
confidence: 85%
“…However, sword bean seeds had the highest cutting strength value compared to velvet bean and other legume species (Figure 11). Previous studies on velvet beans showed that the LD50 was achieved at 281 Gy, and the highest genetic diversity was obtained at 350 Gy [11]. This means that sword bean need a higher gamma-ray radiation dose than 200 Gy to reach the LD50 and plant genetic diversity.…”
Section: Resultsmentioning
confidence: 91%
“…[13] reported that LD50 on KKL-1 lima bean (Phaseolus lunatus) variety in India was 10 kR (100 Gy). While, LD50 on hyacinth bean was reported by [11] and [12]. There were ranged for 281.5 Gy -512 Gy, depend on the variety.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation